PVTCP: Towards practical and effective congestion control in virtualized datacenters - Luwei Cheng; Cho-Li Wang; Lau, Francis C. M. (2013 21st IEEE International Conference on Network Protocols (ICNP), 2013)
While modern datacenters are increasingly adopting virtual machines (VMs) to provide elastic cloud services, they still rely on traditional TCP for congestion control. In virtualized datacenters, TCP endpoints are separated by a virtualization layer and subject to the intervention of the hypervisor's scheduling. Most previous attempts focused on tuning the hypervisor layer to try to improve the VMs' I/O performance, and there is very little work on how a VM's guest OS may help the transport layer to adapt to the virtualized environment. In this paper, we find that VM scheduling delays can heavily contaminate RTTs as sensed by VM senders, preventing TCP from correctly learning the physical network condition. After giving an account of the source of the problem, we propose PVTCP, a ParaVirtualized TCP to counter the distorted congestion information caused by VM scheduling on the sender side. PVTCP is self-contained, requiring no modification to the hypervisor. Experiments show that PVTCP is much more effective in addressing incast congestion in virtualized datacenters than standard TCP.